1996
DOI: 10.1021/jm950588y
|View full text |Cite
|
Sign up to set email alerts
|

(S)-13-[(Dimethylamino)methyl]-10,11,14,15-tetrahydro-4,9:16,21-dimetheno- 1H,13H-dibenzo[e,k]pyrrolo[3,4-h][1,4,13]oxadiazacyclohexadecene-1,3(2H)-dione (LY333531) and Related Analogues:  Isozyme Selective Inhibitors of Protein Kinase Cβ

Abstract: Protein kinase C (PKC) is a family of closely related serine and threonine kinases. Overactivation of some PKC isozymes has been postulated to occur in several diseases states, including diabetic complications. Selective inhibition of overactivated PKC isozymes may offer a unique therapeutic approach to disease states such as diabetic retinopathy. A novel series of 14-membered macrocycles containing a N-N'-bridged bisindolylmaleimide moiety is described. A panel of eight cloned human PKC isozymes (alpha, beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 312 publications
(84 citation statements)
references
References 28 publications
3
81
0
Order By: Relevance
“…Prkcb is frequently amplified in many malignancies and encodes a kinase that is considered a potential therapeutic target in cancer, diabetes, and heart disease (Mochly-Rosen et al, 2012). We hypothesized that HRas G12V MEFs would be more sensitive to LY333531, a clinically relevant Prkcb inhibitor also known as Ruboxistaurin (Jirousek et al, 1996), than cell lines lacking H3K27ac at the Prkcb locus. Indeed, HRas G12V MEFs were significantly more sensitive to doses of LY333531 ranging from 10-15 μM, compared to Spry124 fl/fl EV or Spry124 −/− EV MEFs (Figures 7A and S7E).…”
Section: Resultsmentioning
confidence: 99%
“…Prkcb is frequently amplified in many malignancies and encodes a kinase that is considered a potential therapeutic target in cancer, diabetes, and heart disease (Mochly-Rosen et al, 2012). We hypothesized that HRas G12V MEFs would be more sensitive to LY333531, a clinically relevant Prkcb inhibitor also known as Ruboxistaurin (Jirousek et al, 1996), than cell lines lacking H3K27ac at the Prkcb locus. Indeed, HRas G12V MEFs were significantly more sensitive to doses of LY333531 ranging from 10-15 μM, compared to Spry124 fl/fl EV or Spry124 −/− EV MEFs (Figures 7A and S7E).…”
Section: Resultsmentioning
confidence: 99%
“…The general PKC inhibitor GF109203x (0.5-5 µM) and that of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 13 calcium sensitive isoforms Gö6976 (3 µM) both reduced the effect of PMA on ACE density without affecting the baseline expression of the enzyme in the absence of PMA. LY 379196 is a close analog of GF 109203x that has been developed [15]. It had no effect of PMA-induced ACE regulation in a concentration range that is believed to be isoformspecific.…”
Section: Further Characterization Of Signaling Pathways That Affect Amentioning
confidence: 99%
“…Nevertheless, as it is shown in figure 4, neither the PKC-β inhibitor RBX nor the general PKC inhibitor GFX was able to inhibit the H 2 O 2 -induced eNOS Thr 495 phosphorylation seen in HUVEC cells. Although RBX was used in a relatively low concentration (50 n M ) in our experiments compared to other studies, the used concentration is approximately 10 times higher than the IC 50 value first described by Jirousek et al [43] and is therefore supposed to completely inhibit the action of both PKC-βI and PKC-βII [42]. The concentration of the general PKC inhibitor GFX of 1 µ M used in our study was well over the reported IC 50 value of 10 n M [42] and we would therefore have expected an effect if PKC was involved in H 2 O 2 -mediated Thr 495 phosphorylation.…”
Section: Discussionmentioning
confidence: 83%